Radiological imaging of choroid plexus tumors: Systematic approach toward diagnosing a choroid plexus tumor - Chakshu, Batra; Neeru, Kapur (Indian Journal of Case Reports, 2021)
Choroid plexus tumors (CPTs) are rare intraventricular tumors comprising approximately 1% of all brain tumors. The common locations are the lateral ventricle (most common location in children), the third and fourth ventricles (most common location in adults), and cerebellopontine angle. Here, we present the case of a 10-month-old child with complaints of fever (99.6F), abnormal eye movements, and bilateral papilledema. Ultrasound cranium of the child revealed a well-defined hyperechoic lesion adjacent to the trigone and occipital horn of the right lateral ventricle. No vascularity could be appreciated on color Doppler. Non-contrast computed tomography of the brain showed a well-defined lobulated mass lesion epicentered at the choroid plexus of the right lateral ventricle which was hyperdense relative to the brain parenchyma with specks of calcification. Contrast-enhanced magnetic resonance imaging showed a solid intensely enhancing lobulated mass lesion with frond-like morphology originating from the choroid plexus of the occipital horn of the right lateral ventricle. Surgical excision of the CPT was done under aseptic conditions. We try to reinforce the ultrasound (USG), CT, and MRI findings of a CPT which ultimately came out to be a choroid plexus papilloma (CPP) on histopathological examination.